Reduced graphene/nanostructured cobalt oxide nanocomposite for enhanced electrochemical performance of supercapacitor applications - Sagadevan, Suresh; Marlinda, Ab Rahman; Johan, Mohd Rafie; Umar, Ahmad; Fouad, H.; Alothman, Othman Y.; Khaled, Usama; Akhtar, M.S.; Shahid, M.M. (Elsevier, 2020)
We demonstrate the preparation of nanostructures cobalt oxide/reduced graphene oxide (Co3O4/rGO) nanocomposites by a simple one-step cost-effective hydrothermal technique for possible electrode materials in supercapacitor application. The X-ray diffraction patterns were employed to confirm the nanocomposite crystal system of Co3O4/rGO by demonstrating the existence of normal cubic spinel structure of Co3O4 in the matrix of Co3O4/rGO nanocomposite. FTIR and FT-Raman studies manifested the structural behaviour and quality of prepared Co3O4/rGO nanocomposite. The optical properties of the nanocomposite Co3O4/rGO have been investigated by UV absorption spectra. The SEM/TEM images showed that the Co3O4 nanoparticles in the Co3O4/rGO nanocomposites were covered over the surface of the rGO sheets. The electrical properties were analyzed in terms of real and imaginary permittivity, dielectric loss and AC conductivity. The electrocatalytic activities of synthesized Co3O4/rGO nanocomposites were determined by cyclic voltammetry and charge-discharge cycle to evaluate the supercapacitive performance. The specific capacitance of 754 Fg−1 was recorded for Co3O4/rGO nanocomposite based electrode in three electrode cell system. The electrode material exhibited an acceptable capability and excellent long-term cyclic stability by maintaining 96% after 1000 continuous cycles. These results showed that the prepared sample could be an ideal candidate for high-energy application as electrode materials. The synthesized Co3O4/rGO nanocomposite is a versatile material and can be used in various application such as fuel cells, electrochemical sensors, gas sensors, solar cells, and photocatalysis. © 2019 Elsevier Inc.